2006
DOI: 10.1007/s00383-006-1717-5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric splenectomy for hematological diseases: outcome analysis

Abstract: IntroductionSpleen produces specific antibodies and filters out encapsulated organisms and, therefore, is important in protecting the body against infection. On the other hand, splenectomy is a widely used therapeutic modality in the management of a variety of hematological disorders. The current surgical options for this purpose include not only the novel modalities like partial splenectomy, splenic embolization, or laparoscopic splenectomy but also the traditional open splenectomy [1,2]. However, most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
7
0
4
Order By: Relevance
“…However, long-term antibiotic therapy may be a risk factor for the selection of resistant strains, and efficacy may be reduced by noncompliance. On the other hand, all cases of OPSI reported in the literature are due to noncompliance of patients or splenectomized children's parents, such as the 9-year-old thalassemic child reported by Durakbasa et al 80 In this case, the postmortem inquiry revealed that after being sent home following the operation, the patient had not been given any penicillin medication. In the same study, a boy with elliptocytosis died of overwhelming postsplenectomy sepsis 6 years after the operation while still on penicillin prophylaxis.…”
Section: Managementmentioning
confidence: 87%
See 2 more Smart Citations
“…However, long-term antibiotic therapy may be a risk factor for the selection of resistant strains, and efficacy may be reduced by noncompliance. On the other hand, all cases of OPSI reported in the literature are due to noncompliance of patients or splenectomized children's parents, such as the 9-year-old thalassemic child reported by Durakbasa et al 80 In this case, the postmortem inquiry revealed that after being sent home following the operation, the patient had not been given any penicillin medication. In the same study, a boy with elliptocytosis died of overwhelming postsplenectomy sepsis 6 years after the operation while still on penicillin prophylaxis.…”
Section: Managementmentioning
confidence: 87%
“…Moreover, this technique does not abolish the risk of gallstone formation in patients suffering from hemolytic anemia. 80 There are a few cases where PS could be the best compromise, eg, children younger than 2 years who are unable to be vaccinated or patients living in countries where antipneumococcal vaccination is not available.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The study comprised 14 girls and 5 boys, showing female preponderance. In a study undertaken by Durakbasa et al (2006) [1] showed female preponderance. Krishna et al (1987) [9] reviewed 13 patients with hematological disorders, of whom 12 were male children and one female, showing male preponderance.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of the spleen decreases the risk of early surgical complications such as adjacent organ injury, wound infection, pancreatitis, pleural effusion, and atelectasia as well as late splenectomy complications such as sepsis, serious infections and thromboembolic events. [1,2] Generally, splenectomy is an easy operation for trauma surgeons, while preservation of the spleen is a more laborious procedure. On the other hand, preserving the spleen is important in terms of early-and late-period outcomes.…”
Section: Sonuçmentioning
confidence: 99%